Styles of play in professional soccer: an approach of the Chinese Soccer Super League - Lago-Peñas, C.; Gómez-Ruano, M.; Yang, G. (International Journal of Performance Analysis in Sport, 2017)
Describing and measuring different styles of play that soccer teams can adopt during a match is a very important step towards a more predictive and prescriptive performance analysis. The current study aimed to identify and measure different styles of play in professional soccer. The sample comprises all 240 matches in the Chinese Soccer Super League during the 2016 season. Data were examined using a linear regression analysis and a factor analysis. Five factors had eigenvalues greater than 1 and explained 79.6% of the total variance. The following styles of play were found: Factor 1 ("possession" style of play, correlated with the ball possession, ball possession in opponent half and in the final third of the field, positional attacks, passes, accurate passes, passes forward and back), Factor 2 (set pieces attack, correlated positively with the number of set pieces attacks, and attacks), Factor 3 (counterattacking play, correlated with interceptions, interceptions in opponents half, recovered balls, and number of counterattacks) and Factor 4 and 5 (transitional play, correlated with lost balls, and picking up free balls). These metrics may allow coaches and analysts to classify the teams` into specific profiles of playing styles.